validasi - Rika anggraini; Rita Hairani; Aman Sentosa Panggabean (JURNAL KIMIA MULAWARMAN, 2018)
The research about validation of the method of Hg determination on the sample from wastewater treatment plant (WWTP) PT. Badak NGL Bontang, Kalimantan Timur using cold vapour-atomic absorption spectrophotometer (CV-AAS) techniques has been conducted. To obtain a valid measurement result, determinations of the important several parameters that influence the method validation are used. The results of research showed that 20% SnCl2 solution could be used as a reducing agent. The analytic performance of measurement obtain is good, showed with the linearity (r) value ≥ 0.995, LOD was 0.2530 ppb, LOQ was 0.8432 ppb, MDL was 0.6427 ppb and repeatability and reproducibility are shown as % RSD < 2/3 CV Horwitz values. The accuracy of this method is very good with a percentage of recovery value of 114.88%. Based on the results of this research, CV-AAS method can be used in the determination of Hg in WWTP samples with the valid results.